Strategy Development Model in the Trangsan Gatak Sukoharjo Furniture Industry: Model Pengembangan Strategi di Industri Furnitur Trangsan Gatak Sukoharjo - Hakim, Lukman; Padmantyo, Sri; Irawatiama, Zulfa; Maimunu, M. Halim (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Organizations must continually make changes in order to face various challenges whose form, type and intensity have never occurred before. In this case, organizational change is a business demand that companies must implement when they want to improve their company's performance. The aim of this research is: Developing a model for developing organizational change strategies in the furniture industry in Trangsan Gatak Sukoharjo. The research results concluded that the strategy development model for the Trungsan Gatak Sukoharjo furniture industry includes: (1) Production Strategy by utilizing knowledge (science) and technology, implementing new unique designs and styles of furniture, and conducting research so that products do not become outdated. (2) Marketing Strategy by increasing overseas marketing reach, furniture selling price policies, expanding the network of agents and distributors abroad. (3) Financial strategy by entering into partnerships with state-owned companies, banking and sharia banking to increase industrial capital as well as increasing partnerships with the government to develop the revitalization area for the Trungsan furniture village. (4) HR strategy by means of: IT training. IT Training. training on furniture product creation and recruitment of accounting personnel.